Study of iron benzoate as a novel steel corrosion inhibitor pigment for protective paint films - Blustein, Guillermo (2007)
The aim of this work was to study the lab-synthesized iron benzoate as a novel steel corrosion inhibitor pigment to formulate anticorrosive paint films. The iron benzoate anticorrosive properties were studied by electrochemical and spectroscopic essays employing pigment suspensions. In a second stage, it was evaluated the performance of anticorrosive paint films containing iron benzoate by accelerated (salt spray and humidity chambers) and EIS tests. The protective layer nature grown under the paint films in the salt spray chamber was also assessed. Experimental results shown that ferric benzoate was adequate to formulate anticorrosive paint films with improved anticorrosive assessed